Penerapan Metode TOPSIS dalam Pemilihan Moda Transportasi Berkelanjutan untuk Pengurangan Emisi Gas Rumah Kaca - Pramita, Galuh; Darwis, Dedi (Forum Kerjasama Pendidikan Tinggi, 2024)
The choice of sustainable modes of transportation for the reduction of greenhouse gas emissions is an important aspect in efforts to mitigate climate change. By choosing environmentally friendly modes of transportation, such as public transportation, electric vehicles, bicycles, or ride-sharing, individuals and organizations can contribute significantly to the reduction of greenhouse gas emissions produced by the transportation sector. The research objective of the application of decision support systems in the selection of sustainable modes of transportation for the reduction of greenhouse gas emissions is to provide a structured and effective framework in assisting individuals and organizations in choosing alternative modes of transportation that best suit their needs while also minimizing negative impacts on the environment. DSS can be a very useful tool in the selection of sustainable modes of transportation for the reduction of greenhouse gas emissions. DSS can integrate various factors such as energy efficiency, greenhouse gas emissions, infrastructure accessibility, and cost to determine the mode of transportation that best suits user needs and preferences. The ranking results are based on the respondents' assessment data for rank 1 with a final score of 0.92974 with an alternative name for Bicycles, rank 2 with a final score of 0.78159 with an alternative name for Hydrogen-Based Public Transportation, rank 3 with a final score of 0.76089 with an alternative name for Public Transportation, and rank 4 with a final score of 0.15703 with an alternative name for Electric Vehicles. The results of processing respondent response data based on 4 TRITAM Model criteria obtained Trust results of 76.25%, Risk of 75%, Perceived usefullness of 93.96%, Perceived easy of Use of 82.92%. Of the overall criteria of the TRITAM Model for technology acceptance, the result was very good at 84.17%